2015
DOI: 10.1063/1.4905781
|View full text |Cite
|
Sign up to set email alerts
|

N-channel field-effect mobility inversely proportional to the interface state density at the conduction band edges of SiO2/4H-SiC interfaces

Abstract: We investigated the effects of the interface state density (DIT) at the interfaces between SiO2 and the Si-, C-, and a-faces of 4H-SiC in n-channel metal-oxide-semiconductor field-effect transistors that were subjected to dry/nitridation and pyrogenic/hydrotreatment processes. The interface state density over a very shallow range from the conduction band edge (0.00 eV < EC − ET) was evaluated on the basis of the subthreshold slope deterioration at low temperatures (11 K < T). The interface state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 28 publications
2
31
0
Order By: Relevance
“…6 They could be fully eliminated by optimum POAs by NO or POCl 3 . Based on the similarities between our ESR data and previous electrical characterization, 2,3,9,12 we suggest that the interface carbon defects are the major electron traps at the dry-oxidized 4H-SiC(0001)/SiO 2 interfaces, and hence both the POAs drastically improve l FE of Si-face 4H-SiC MOSFETs. In addition, we found that the POCl 3 POAs at 1000 C formed a high density (>1 Â 10 12 cm À2 ) of the P donors in the channel region, which is possibly related to further enhancement on l FE.…”
Section: Resetsupporting
confidence: 84%
See 2 more Smart Citations
“…6 They could be fully eliminated by optimum POAs by NO or POCl 3 . Based on the similarities between our ESR data and previous electrical characterization, 2,3,9,12 we suggest that the interface carbon defects are the major electron traps at the dry-oxidized 4H-SiC(0001)/SiO 2 interfaces, and hence both the POAs drastically improve l FE of Si-face 4H-SiC MOSFETs. In addition, we found that the POCl 3 POAs at 1000 C formed a high density (>1 Â 10 12 cm À2 ) of the P donors in the channel region, which is possibly related to further enhancement on l FE.…”
Section: Resetsupporting
confidence: 84%
“…The POA process can make the field-effect mobility (l FE ) of 4H-SiC MOSFETs ten times larger than that before the POA. 1,2 The mechanism for this drastic l FE -improvement has recently been clarified by combining Hall and split capacitance-voltage measurements. 3 According to the recent findings, the NO POA process effectively increases the amount of free electrons by removing electron traps, while it does not increase the electron mobility itself much.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 The standard method for fabricating good 4H-SiC/SiO 2 interfaces is thermal oxidation by dry O 2 gas (dry oxidation) followed by interfacial nitridation such as NO post-oxidation anneal (POA). 2 This process can reduce shallow interface states near the conduction band edge (E C ) 2,3 and deeper electron traps, 4 resulting in a drastic improvement on the field-effect mobility (μ FE ) of SiC-MOSFETs. As a result, the improved μ FE reaches 30-40 cm 2 V −1 s −1 for 4H-SiC(0001) (so-called "Si face") MOS interfaces, realizing ultra-low-energy-loss performances of power SiC-MOSFETs as compared to those of conventional power Si-MOSFETs.…”
Section: Introductionmentioning
confidence: 99%
“…Low channel performance at SiO 2 /4H-SiC interfaces due to a high interface state density (D IT ) 1 and low channel mobility has been a problem of both scientific and practical interest. 2 Although SiC is advantageous in that SiO 2 can be formed by oxidation, improvement of the SiO 2 /4H-SiC channel performance has plateaued, despite intensive research and development efforts.…”
Section: Introductionmentioning
confidence: 99%